Critical thinking and reflection in contemporary mental health care: A Foucauldian perspective. (October 2016) - Roberts, Marc
Highlights: Mental health practitioners need to possess critically reflective capacities. The development of these capacities can be situated in the work of Foucault. Such capacities can be obstructed by a sense that some things are 'self-evident'. There is a need to historicise the theory and practice of mental health care. There is a need to politicise the theory and practice of mental health care.